Evaluation of advanced sorghum breeding lines for grain mold resistance - R.B. SOLUNKE3 and BHARATI BHAT4, R.P. THAKUR1*, BELUM V.S. REDDY1, V.P. RAO1, G.D. AGARKAR2, (Indian Phytopathology, 2009)
Grain mold, caused by a fungal complex, is a major production constraint of early-maturing highyielding rainy season sorghum (Sorghum bicolor) hybrids. A total of 34 selected elite B-lines bred for grain mold resistance at ICRISAT were evaluated for their resistance stability through a collaborative Sorghum Grain Mold Resistance Stability Nursery under natural infection at five locations (Akola, Parbhani, Palem, Patancheru, and Surat) in India during three rainy seasons, 2002 to 2004. Grain mold severity scores were recorded at two stages, first at physiological maturity- panicle grain mold rating (PGMR) in the field nursery and second after harvest on threshed grain- threshed grain mold rating (TGMR), using a progressive 1–5 scale. Results indicated significant differences among the genotypes (G), locations (L), years (Y) and their interactions for both PGMR and TGMR scores. A strong positive correlation (r = 0.89) between PGMR and TGMR indicated the adequacy of grain mold severity recording, preferably PGMR. Relatively, larger variance due to G than to G × L and G ×Y interaction components justified breeding sorghum hybrid for grain mold resistance for wider adaptation in India.